Cycling Demonstration Towns. Development of Benefit-Cost Ratios. February 2010. - (:unkn) unknown (My University, 2010)
The analysis builds upon the recently published monitoring reports which found that on average cycling rates increased by 27% in the Cycling Demonstration Towns and that the health benefits (from reduced mortality) were worth around £2.50 for every £1 spent. In particular this paper attempts to produce a Benefit-Cost Ratio (BCR) of the programme consistent with the analytical approach used by the Department for Transport (DfT) to appraise business cases. This approach provides an assessment of the impact of the Cycling Demonstration Towns on a range of objectives such as congestion relief and improved journey ambience.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrsinvestition; Statistik; Mobilitätsverhalten; Fahrradbenutzung; Fahrradförderung; Verkehrsunfall; Mobilitätsförderung; Verkehrsförderungsprogramm; Projekt